Analysis of carrier injection in Si nanoparticle‐SiOx film based MOS devices. Issue 2 (23rd January 2014) - Jacques, E.; Pichon, L.; Labbe, C.; Khomenkova, L.; Gourbilleau, F.
Abstract The electrical properties of silicon rich oxide (SRO) layers integrated in metal‐oxide‐semiconductor device are analysed. The layers are deposited using the magnetron co‐sputtering of a pure SiO2 and Si targets under a pure argon plasma. Each SRO layer embedding silicon nanoparticles (Si‐np‐SiOx) was subsequently submitted to an optimized annealing treatment. Three types of Al/Si‐np‐SiOx/p‐Si devices are fabricated with different incorporated silicon excesses (9, 11, or 16 at.%) in the active layer. Analysis of static electrical properties of the devices showed a semi‐resistive behaviour for each device. Carrier injection into the SiOx matrix in terms of Poole‐Frenkel and Fowler‐Nordheim mechanisms is analysed in relation with the incorporated silicon excess. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)